Vocabulary and Gist Reading - Reyes, Susana; Briones, Susana; Pocovi, Martha Botto de; Fortuny, Liliana; Sastre, Silvia (The ESPecialist, 2012)
This paper deals with the role of vocabulary in ESP reading. Different types of lexical repetition patterns are presented to show their importance in the hierarchization of the information. This is demonstrated by analysing a text following the framework developed by Hoey (1991). Some activities designed to raise student’s awareness of vocabulary relations in the building of meaning are presented as well as conclusions about the importance of vocabulary.